Aspects of ischemic stroke biomechanics derived using ex-vivo and in-vitro methods relating to mechanical thrombectomy. (January 2022) - McCarthy, Ray; Mirza, Mahmood; Johnson, Sarah; Dwivedi, Anushree; Gunning, Gillian; Vale, David; Gilvarry, Michael
Abstract: Establishing the underlying biomechanics of acute ischemic stroke (AIS) and its treatment is fundamental to developing more effective clinical treatments for one of society's most impactful diseases. Recent changes in AIS management, driven by clinical evidence of improved treatments, has already led to a rapid rate of innovation, which is likely to be sustained for many years to come. These unprecedented AIS triage and treatment innovations provide a great opportunity to better understand the disease. In this article we provide a perspective on the recreation of AIS in the laboratory to inform contemporary device design and procedural techniques in mechanical thrombectomy. Presentation of these findings, which have been used to solve the applied problem of designing mechanical thrombectomy devices, is intended to help inform the development of basic biomechanics solutions for AIS.